Respuesta agronómica del frijol cuarentón (Phaseolus vulgaris L.) con abonos orgánicos en dos pisos climáticos diferentes. - Galarza Baque, Jordy Reinaldo (2023)
The present research project was carried out in the areas of the Valencia and Ventanas cantons, to evaluate the agronomic response of the forty-year-old bean (Phaseolus vulgaris L.) from the Red kidney variety through the application of organic foliar fertilizers. The following objectives were proposed: Determine the agronomic responses of forty-year-old beans in two different climatic floors, identify the appropriate dose of foliar organic fertilizers on the forty-year-old bean crop and analyze the cost of applying organic fertilizers in the forty-year-old bean crop.In this way, a Completely Randomized Block Design (DBCA) was implemented with five treatments and three repetitions. The following agronomic parameters were evaluated such as: germination percentage, plant height, days to flowering, days to pod formation, number of pods, days to harvest, grain weight per plant under study, net weight of kg /plot and also an economic analysis of the study was carried out. The results achieved in the germination percentage for the Valencia canton obtained 94 % for the height of the plant. T4 shows the highest values with 10.55; 23.10 and 31.40 cm at 15, 30 and 45 days after being evaluated; referring to days to flowering T4 got higher results with 29.90. Respecting to the formation of pods T4 presented 33.50 days for the number of pods and it is considered the best indicator of pods with 6.15; Its harvest was evaluated and T4 registered 42.45 days, its weight per plant under study. T4 maintained better results with 18.94 gr per plant, while the highest yield per plot occurred with T4, with 1.29 kg/plot. In the same way, the germination percentage was seen for the Cantón Ventanas expressing 95% and in the plant height with better averages of 10.60; 22.90 and 32.40 cm at 15, 30 and 45 days after being evaluated by T4; in days to flowering it was obtained by T4 with 29.00; the formation of pods was presented in T3 with 36.25 days for the number of pods it was recorded that the reflex T4 with the best indicator of pods with 15.75; Its harvest was evaluated that T4 registered 44.45 days, its weight per plant under study, T4 maintained better results with 32.24 g per plant, while the highest yield per plot occurred with T4, with 88.00 kg/ha. . The economic analysis indicates that T4 reach UDS 220.00 as benefit.